From disease management to prevention, hip prosthesis joint infections in the past 20 years: a global research trends and top 10 cited articles analysis - Fei-Long Li; Fei-Long Li; Xing-Yu Qi; Jin-Lun Chen; Yi-Rong Zeng; Yi-Rong Zeng (Frontiers in Surgery)
BackgroundThere are few literatures comprehensively analyzed the global research in hip prosthesis joint infections (HPJI). We aim to clarify the global research trends and analysis the top 10 cited articles in the HPJI field.MethodsWe identified the core collection of articles/reviews in the HPJI field from 2001 to 2021 through the Web of Science Core Collection (WOSCC). VOSviewer and online bibliometric tool were used to conduct the visualized and knowledge maps. Annual trends of publications, research hotspots and the top 10 cited articles were analyzed.ResultsA total of 5,477 publications were finally included. Generally, an increasing trend was observed in the number of publications from 2001 to 2021. The authors, journals and institutions with largest number of publications all belong to the USA. Co-occurrence analysis of keywords showed that surgical techniques, risk factors, revision surgery strategy, epidemiology, diagnoses and prevention were the 6 major research directions. Total hip arthroplasty, replacement, outcomes, risk factors and diagnosis were the keywords that occurred most frequently. The top 10 cited articles were all published in Journal Citation Reports (JCR) Q1 journals, providing valuable reference value from the perspectives of clinical guidelines, perioperative management, causes and diagnostic methods of infection, epidemiological investigation, risk factors and prognostic analysis.ConclusionsThe number of publications in HPJI field had been on the rise over the past 20 years, from disease management to prevention. An intensive reading of the top 10 cited articles is beneficial to understand the focus of HPJI research comprehensively.